The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jmcb.12013
|View full text |Cite
|
Sign up to set email alerts
|

Core Measures of Inflation as Predictors of Total Inflation

Abstract: Policymakers tend to focus on core inflation measures because they are thought to be better predictors of total inflation over time horizons of import to policymakers. We find little support for this assumption. While some measures of core inflation are less volatile than total inflation, core inflation is not necessarily the best predictor of total inflation. The relative forecasting performance of models using core inflation and those using only total inflation depends on the inflation measure and time horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 19 publications
(20 reference statements)
5
32
1
Order By: Relevance
“…A good example of the differing views regarding headline and core inflation can be found by comparing Smith () and Crone et al. (). While the former argues in favor of using core inflation to forecast the rate of inflation in the U.S. the latter holds that core inflation is not necessarily the best predictor of total inflation and that the forecasting performance depends on the inflation measure and forecasting horizon.…”
mentioning
confidence: 99%
“…A good example of the differing views regarding headline and core inflation can be found by comparing Smith () and Crone et al. (). While the former argues in favor of using core inflation to forecast the rate of inflation in the U.S. the latter holds that core inflation is not necessarily the best predictor of total inflation and that the forecasting performance depends on the inflation measure and forecasting horizon.…”
mentioning
confidence: 99%
“…According to Crone, Khettry, Mester and Novak (2013) this is the prevailing view. In fact, food and energy components have been historically highly volatile (for example, due to temporary supply disruptions), and their large price fluctuations are usually expected to correct themselves within a relatively short period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Meyer and Pasaogullari (2010) …nd the median and the 16% trimmed-mean CPI forecast year-ahead headline in ‡ation about as well as in ‡ation expectations do, and outperform simple forecasting models. Crone, Khettry, Mester, and Novak (2013) found that over longer-horizons (i.e. 24-months), the median CPI yields a forecast signi…cantly superior to that of the headline or ex food and energy CPI index.…”
Section: Introductionmentioning
confidence: 95%
“…The lowest RMSE belongs to x 43;49 , which is the trimmed-mean CPI that excludes 43 percent of the lower tail and nearly all (49 percent) of the upper tail. The contour plot reveals a small area (in royal blue), just shy of the symmetric trim (the black line) where all of these trimmed-mean measures have a RMSE between 2.0 and 2.5 11. That next swath (lighter blue) ranges from a RMSE of 2.5 and 3.0.…”
mentioning
confidence: 96%